2016
DOI: 10.1037/pag0000139
|View full text |Cite
|
Sign up to set email alerts
|

Habitual attention in older and young adults.

Abstract: Age-related decline is pervasive in tasks that require explicit learning and memory, but such reduced function is not universally observed in tasks involving incidental learning. It is unknown if habitual attention, involving incidental probabilistic learning, is preserved in older adults. Previous research on habitual attention investigated contextual cuing in young and older adults, yet contextual cuing relies not only on spatial attention but also on context processing. Here we isolated habitual attention f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 46 publications
(75 reference statements)
3
26
0
Order By: Relevance
“…In contrast to the results from Jiang et al (2016) suggesting that aging may tip the balance of attention from goal-driven to habitual attention, neuroimaging studies have shown agerelated decline in the function of a brain region important for habit formation-namely the basal ganglia (for review, see Howard & Howard, 2013). Tasks that depend on basal ganglia function, such as learning a probabilistic sequence, are performed more poorly by older than young adults (Howard, Howard, Dennis, Yankovich, & Vaidya, 2004).…”
mentioning
confidence: 86%
See 3 more Smart Citations
“…In contrast to the results from Jiang et al (2016) suggesting that aging may tip the balance of attention from goal-driven to habitual attention, neuroimaging studies have shown agerelated decline in the function of a brain region important for habit formation-namely the basal ganglia (for review, see Howard & Howard, 2013). Tasks that depend on basal ganglia function, such as learning a probabilistic sequence, are performed more poorly by older than young adults (Howard, Howard, Dennis, Yankovich, & Vaidya, 2004).…”
mentioning
confidence: 86%
“…Two lines of previous research suggest that, relative to young adults, older adults are more likely to rely on search habits than task instructions. First, as shown in Jiang et al (2016), location probability learning is preserved in older adults, even though their search is less efficient relative to young adults. Second, research on age differences in the use of spatial reference frames suggests that aging has a more detrimental effect on environment-centered coding than viewer-centered coding.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…First, secondary working-memory load impairs goal-driven attention but does not interfere with location probability learning (Won & Jiang, 2015). Second, whereas goal-driven attention is less efficient in older adults than in young adults, location probability learning is insensitive to aging (Jiang, Koutstaal, & Twedell, 2016). Third, whereas an endogenous spatial cue induces a baseline shift of attention, location probability learning does not (Addleman, Schmidt, Remington, & Jiang, 2019).…”
Section: Traditional Definitions Of Early-and Late-locus Accountsmentioning
confidence: 98%